2017
DOI: 10.1007/s10856-017-5935-2
|View full text |Cite
|
Sign up to set email alerts
|

Spine rod straightening as a possible cause for revision

Abstract: In a previous study, the authors examined the elastic and short-term anelastic springback of Ti6Al4V, CoCrMoC and A316L stainless steel spine rods to observe how the rods mechanically respond in OR contouring. In that study rods were 200 mm long and only the movement at the tip was recorded. The implication of that work was that rods will straighten in-vivo, however, in order for the mechanism of straightening to be determined, the movement of individual bends over time must first be elucidated. Spine rods use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…More recent studies have shown flattening of rods after implantation in spinal deformity patients. 21 So even if a rod from the standard set is further bent to create greater lordosis, the possibility of an iatrogenic fusion in a flat position may still exist. The smaller radius of curvature in a PSSR maintains and may better match the lumbar curve, potentially improving quality of life outcomes and decreasing the potential for complications.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown flattening of rods after implantation in spinal deformity patients. 21 So even if a rod from the standard set is further bent to create greater lordosis, the possibility of an iatrogenic fusion in a flat position may still exist. The smaller radius of curvature in a PSSR maintains and may better match the lumbar curve, potentially improving quality of life outcomes and decreasing the potential for complications.…”
Section: Discussionmentioning
confidence: 99%
“…While these material properties can be easily measured in a laboratory setting the theoretical implications cannot necessarily be transferred to the clinical reality. Furthermore, Ayers et al [ 20 ] found that the biomechanical profile of a given rod was very sensitive to differences in production as individual properties varied greatly between manufacturers for the same material. Pienkowski et al [ 21 ] showed that fatigue life of the implant was explained by implant type rather than material further adding to the complexity of understanding rod biomechanics.…”
Section: Biomechanical Propertiesmentioning
confidence: 99%
“…However, the potential impact of rod material properties observed in the laboratory setting are not easily extrapolated to the clinical reality [ 94 ]. The clinical performance of spinal rods is susceptible to a complicated interplay of patient, surgeon, and environmental factors [ 95 , 96 ]. It is possible the answer lies in other combinations of stiffness and bending yield strength.…”
Section: Discussionmentioning
confidence: 99%